Race-based trauma and post-traumatic growth through identity transformation - Chin, Dorothy; Smith-Clapham, Amber M.; Wyatt, Gail E. (Frontiers in Psychology, 2023)
Race-based trauma has been linked to multiple adverse health and mental health outcomes, including hypertension, post-traumatic stress, anxiety, and depression. While the possibility of post-traumatic growth (PTG) has been investigated following other types of trauma, relatively less work has been done on PTG following race-based trauma. In this article, we present a theoretical framework integrating three areas of research: race-based trauma, PTG, and racial identity narratives. Based on the work on Black and Asian American identity and integrating theory and research on historical trauma and PTG, this framework posits that the transformation of externally imposed narratives into more authentic, internally generated ones can serve as an important influence that sparks PTG after racial trauma. Based on this framework, strategies and tools that enact the cognitive processes of PTG, including writing and storytelling, are suggested as ways to promote post-trauma growth in response to racial trauma.